Educational Streams and Curriculum (Aliran-Aliran Pendidikan dan Kurikulum) - Sajidatul Aulia; Farhan (Penerbit Hellow Pustaka, 2025)
Education plays a crucial role in shaping the personality of individuals and groups, as outlined in Law Number 20 of 2003 on the National Education System. Education is systematically designed to develop students' potential in various aspects, including spirituality, personality, intelligence, and skills. Over time, education continues to evolve in response to social, cultural, scientific, and technological dynamics. This has given rise to various educational thought schools that reflect responses to the changing needs of society. Since the beginning of civilization, educational schools of thought have been an ongoing discourse, generating new ideas in response to previous ones. Understanding these schools of thought provides educators with historical insights, helping them comprehend the connections between past experiences, current needs, and future anticipations, and apply them within the context of contemporary education.